2008
DOI: 10.1021/jp710268r
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Spectroscopic Properties of Sodium Bromide Aerosols

Abstract: The infrared extinction spectra of aqueous NaBr aerosols at ambient temperature have been measured as a function of relative humidity. Submicron-sized aerosol particles atomized from aqueous NaBr solutions at various concentrations are dried and/or mixed with nitrogen at different humidities and spectroscopically monitored as they flow through an infrared absorption cell. Estimated dry particle median diameters range from 0.24 to 0.15 microm, as calculated from Mie extinction theory. Measured deliquescence and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…7 data, NaBr / HA particles deliquesce at somewhat higher RH than pure NaBr particles: liquid water in NaBr / HA particles is not detected until 50 % RH. This value does not change with the degree of coating, and contrasts with the value of DRH = 37 % for pure NaBr particles (Minambres et al, 2008). On the other hand, OA and LA as surfactants do not have any effect on the deliquescence behaviour of NaBr.…”
Section: Deliquescence and Efflorescence Curvesmentioning
confidence: 54%
“…7 data, NaBr / HA particles deliquesce at somewhat higher RH than pure NaBr particles: liquid water in NaBr / HA particles is not detected until 50 % RH. This value does not change with the degree of coating, and contrasts with the value of DRH = 37 % for pure NaBr particles (Minambres et al, 2008). On the other hand, OA and LA as surfactants do not have any effect on the deliquescence behaviour of NaBr.…”
Section: Deliquescence and Efflorescence Curvesmentioning
confidence: 54%
“…As the optical constants of succinic acid are not available, the scattering contibution of the liquid water extinction spectrum has been removed by simply subtracting the sloping baseline present at high wavenumbers to obtain integrated absorbances à H 2 O . We have checked that this method yields approximate results from our previous Mie calculations in aqueous aerosols . The absorption cross section for dissolved succinic acid has been computed from the integrated absorbance of an aqueous solution of succinic acid of known composition in an infrared cell for liquid samples in the 1118.6−1305.06 cm −1 interval.…”
Section: Resultsmentioning
confidence: 99%
“…Figure sketches the experimental arrangement used . Mixed aqueous solutions of succinic acid (SA) and ammonium sulfate (AS) are formed by dissolving the corresponding solids (SA: Sigma-Aldrich, ≥99.0%; AS: Alfa Aesar, 99.95%) into deionized water at concentrations ranging from 0.02 to 0.05 kg of solute per dm 3 of water and different solute mixing ratios.…”
Section: Methodsmentioning
confidence: 99%
“…Unlike NaCl, the deliquescence behavior of NaBr salts (and their mixed components) is not widely known. It has been reported that ion–solvent interactions can have a significant impact on the uptake and spectral signature of these salts with water . Since both Br – and Cl – are both highly polarizable, they interact with water more strongly and show spectral characteristics (shifts, or extra bands) that are different than most binary salts.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that ion−solvent interactions can have a significant impact on the uptake and spectral signature of these salts with water. 25 Since both Br − and Cl − are both highly polarizable, they interact with water more strongly and show spectral characteristics (shifts, or extra bands) that are different than most binary salts. These characteristics were observed in Figure 1C, and the changes in these ion−solvent interactions manifest themselves as changes in the integrated absorbance as a function of RH (Figure 2C).…”
Section: ■ Introductionmentioning
confidence: 99%